2003
DOI: 10.1007/bf03402042
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Early Secretory Antigen Target-6 Epitopes for the Immunodiagnosis of Active Tuberculosis

Abstract: The early secretory antigenic target (ESAT)-6 purified protein and peptides from Mycobacterium tuberculosis were evaluated as antigens for the immunodiagnosis of tuberculosis (TB). Because the control of TB requires improved diagnostic procedures, efforts have increased to identify Mycobacterium tuberculosis-specific epitopes for the immunodiagnosis of active TB and to discriminate between active and latent states of infection. Two multiepitopic peptides from ESAT-6 protein were selected by computational analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
62
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 36 publications
3
62
0
1
Order By: Relevance
“…ESAT-6 is present in M. tuberculosis but absent from all strains of Mycobacterium bovis bacille Calmette-Guérin, as well as in almost all environmental mycobacteria [6,7], although a homologue has been identified in Mycobacterium leprae [8]. On the basis of this line of research, we recently reported an in vitro immune diagnostic ELISPOT assay for IFN-g whose novelty consists of use of ESAT-6 peptides, which are multiepitopic and are selected by computational analysis [9]. This assay's results are positive only for patients with active tuberculosis; it has a sensitivity of 74% and a specificity of 100%, compared with the standard tuberculosis culture method.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…ESAT-6 is present in M. tuberculosis but absent from all strains of Mycobacterium bovis bacille Calmette-Guérin, as well as in almost all environmental mycobacteria [6,7], although a homologue has been identified in Mycobacterium leprae [8]. On the basis of this line of research, we recently reported an in vitro immune diagnostic ELISPOT assay for IFN-g whose novelty consists of use of ESAT-6 peptides, which are multiepitopic and are selected by computational analysis [9]. This assay's results are positive only for patients with active tuberculosis; it has a sensitivity of 74% and a specificity of 100%, compared with the standard tuberculosis culture method.…”
mentioning
confidence: 97%
“…Two M. tuberculosis-specific, ESAT-6-derived peptides (ESAT-6 6-28 and ESAT-6 66-79 ) were selected for their putative HLA class II binding, as described elsewhere [9,11]. Together, the designed peptide epitopes were able to cover 190% of the HLA class II haplotypes present in different human populations (data not shown).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Auch bei Verwendung von nur einem Antigen, ESAT-6, ist die Spezifität mit 91 -100% sehr hoch (4,16,21,22,25,29,33,41,43 …”
Section: Interferon-γ-test Zum Nachweis Mtb-spezifischer T-zellenunclassified